2015
DOI: 10.1002/ijch.201400150
|View full text |Cite
|
Sign up to set email alerts
|

Iminosugars as Immunomodulating Agents: Synthesis and Biological Activities of 1‐Deoxynojirimycin and Related Compounds

Abstract: Iminosugars are an extremely interesting and versatile class of compounds and have many potential therapeutic applications. However, the use of iminosugar derivatives as immunomodulating agents is an area that is less explored. This review describes recent advances in the field of iminosugars as immunomodulating agents with a particular emphasis on 1‐deoxynojirimycin analogues and related compounds. Both chemical and biological aspects concerning their preparation and/or occurrence in nature, as well as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Over the last decades, iminosugars have become the most popular class of carbohydrate-processing enzyme modulators, being able to alter the glycosylation profile of eukaryotic cells, to interfere in carbohydrate and glycoconjugate metabolism, to regulate the folding and transport of glycoproteins, and to stop the interaction mediated by host cell carbohydrates with infective agents. All these abilities allowed relevant applications of these small molecules as immune system modulators [21][22][23], anti-cancer agents [24] and as therapeutic agents for the treatment of lysosomal storage disorders [25][26][27][28][29], a group of more than 50 rare disorders caused by specific mutations in genes encoding lysosomal enzymes and transporters.…”
Section: Iminosugars: Powerful Glycomimeticsmentioning
confidence: 99%
“…Over the last decades, iminosugars have become the most popular class of carbohydrate-processing enzyme modulators, being able to alter the glycosylation profile of eukaryotic cells, to interfere in carbohydrate and glycoconjugate metabolism, to regulate the folding and transport of glycoproteins, and to stop the interaction mediated by host cell carbohydrates with infective agents. All these abilities allowed relevant applications of these small molecules as immune system modulators [21][22][23], anti-cancer agents [24] and as therapeutic agents for the treatment of lysosomal storage disorders [25][26][27][28][29], a group of more than 50 rare disorders caused by specific mutations in genes encoding lysosomal enzymes and transporters.…”
Section: Iminosugars: Powerful Glycomimeticsmentioning
confidence: 99%
“…Several other Figure 1. Selected naturally occurring compounds with a polyhydroxylated piperidine (with at least three OH in ring) See references [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[14] These are for the treatment of various disease such as cancers, viral infections (Dengue, HIV), and cystic fibrosis. [9,15] Iminosugars have also been investigated as immunomodulators, [16] as activity based molecular probes, [17] or in peptidomimetic research. [18] Recently an argument was made for repurposing of miglitol, celgosivir and miglustat for the treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…It can be envisaged that new imino sugars with quaternary centers can be of interest in drug discovery as glycosidase inhibitors, as immunological modulators, as activity based probes or to be used in peptidomimetic research, given they have found applicability as scaffolds in that area . Despite a sustained interest in discovery of drugs based on glycomimetics,, there have been only a few syntheses of imino sugars with quaternary centers.…”
Section: Introductionmentioning
confidence: 99%